Bibliometric Analysis of Brand Purpose - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure, development trends, and research dynamics of brand purpose through a bibliometric approach. Data were collected from the Scopus database covering the period 2000–2026 and analyzed using VOSviewer to generate co-authorship, country collaboration, citation, and keyword co-occurrence networks. The results indicate a significant increase in publications over the last decade, reflecting growing academic and practical interest in purpose-driven branding. The United States and China emerge as dominant contributors, with extensive international collaboration networks. Thematic analysis reveals that brand purpose research is strongly connected to social media, consumer behavior, and marketing, while also expanding into sustainability, ESG, and technological domains such as artificial intelligence. The overlay and density visualizations further demonstrate a shift from traditional branding constructs toward more dynamic, technology-driven, and ethically oriented themes. Despite this progress, the field remains moderately fragmented, with limited contributions from developing regions. This study contributes by providing a comprehensive overview of the evolution and structure of brand purpose research, identifying key trends, influential works, and future research opportunities. The findings offer valuable insights for both academics and practitioners seeking to understand and implement brand purpose strategies in an increasingly complex and socially conscious marketplace.